Implementasi Chatbot Untuk Rekomendasi Tema Tugas Akhir Program Studi Informatika Menggunakan Metode Simple Additive Weight - Salam Aryanto; Anton Setiawan Honggowibowo; Jabbar Akhmad (FORMAT, 2022)
Many of courses that have been taken makes it difficult for students to determine one area to focus on in determining the theme of the final project. The case study of this research is the Informatics Study Program at the Adisutjipto Aerospace Technology Institute, Yogyakarta. For this reason, a chatbot with a decision support system was made using the simple additive weighting (SAW) method which adds up the weights of the performance of each object that is different and has the same opportunity on all the criteria it has. This method requires the process of normalizing the decision matrix (X) to a scale that can be compared with all existing alternative ratings. The number of observation scores is the sum of the scores of each observation statement multiplied by the weight of the score according to the Likert scale. The maximum score is the maximum score on the Likert scale multiplied by the number of questions, so 5 x 9 = 45. The expected score is the maximum score multiplied by the number of respondents, so 45 x 30 = 1,200. Based on the feasibility test of the chatbot system for the final project recommendation using this method, it succeeded in calculating the feasibility of an application of 1074 (89.5%) with the formula for calculating the percentage of eligibility which was tested by 30 students of the 2017 class of Informatic Study Program, Adisutjipto Aerospace Technology Institute.